Surgical Management of a Congenital Panda Nevus With Preexpanded Triple Forehead Flaps and Temporal Island Flap - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
Congenital panda nevus or the divided nevus of the eyelids is a rare form of melanocytic nevus involving both upper and lower eyelids with the risk of future malignant transformation along with the patients' complaints about the cosmetic appearance. Delicate anatomic features of the eyelids and the limited skin redundancy of the periorbital region make the surgical removal and reconstruction difficult, even in mild cases with partial involvement of the eyelids. A case of congenital panda nevus involving upper and lower eyelids, the eyebrow, and part of the malar eminence and the nasal dorsum is presented. A multistaged surgical management of the lesion with staged excision and reconstruction with preexpanded forehead flaps, temporal island flap, and skin grafts is discussed.
Keywords: Panda nevus; divided nevus of the eyelid; eyebrow; forehead flaps; tissue expander; DIVIDED NEVUS; RISK; PIGMENTATION; MELANOMA; EYELIDS; NAEVI